TINJAUAN HUKUM ISLAM TENTANG PERILAKU MASYARAKAT YANG MENGKONSUMSI NARKOTIKA JENIS JAMUR KOTORAN SAPI DI KABUPATEN GOWA - Muh. Fiqih Indrawan; Subehan Khalik (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The massive, systematic, and structured circulation of narcotics hints at the complexity of controlling and overcoming narcotics as a national problem, not to mention the emergence of religious plants that contain intoxicating substances, such as cow dung fungi. This research is qualitative research with normative juridical and syar'i approaches. The results showed that the community and the Gowa Regency government did not know that the type of fungus that grows on cow dung is included in the Narcotics group. The lack of information related to the content of cow dung fungi is caused by the government's slowness in carrying out educational measures and prevention efforts. Although the Qur'an and hadith do not specifically regulate the legal status of cow dung fungus, but its legal status can be determined using the qiyas method, using the rule that everything that intoxicates the law is haram. Because cow dung mushrooms contain intoxicating substances, the law is illegitimate.